Pengembangan Wisata Halal Dengan Analisis SWOT Dalam Meningkatkan Pertumbuhan Ekonomi Di Daerah Bengkulu - Sari, Nadia Yupita; Sapa Ardesta, Pauta; Hak, Nurul (Pakis Journal Institute, 2024)
Abstract Currently, halal tourism is a very promising global trend. With the largest Muslim population in the world, Indonesia has great potential to become a major player in this field. With its natural beauty still preserved and its extraordinary cultural wealth, Bengkulu has excellent opportunities. to support the development of halal tourism. The aim of this research is to analyze in depth the potential of Bengkulu's halal tourist destinations. By using the SWOT approach, we want to determine the strengths, weaknesses, opportunities and difficulties that Bengkulu faces when developing this industry. It is hoped that the findings of this research can provide suggestions on how to maximize the potential of halal tourism, thereby contributing to the economic growth of the people of Bengkulu. According to research results, Bengkulu has many opportunities to develop into an attractive halal tourist destination. Cultural richness, environmental beauty, and the possibility of halal culinary delights can become capital.